Evidence Tables for Guidelines for the Rehabilitation of Patients with Metastatic Spinal Cord Compression (MSCC) : Assessment and Care Provision by Occupational Therapists and Physiotherapists In the Community Setting (Northern Ireland).: Assessment and Care Provision by Occupational Therapists and Physiotherapists In the Community Setting (Northern Ireland). ([2017]) - Northern Ireland., Regulation; Quality Improvement Authority
No abstract available